Causative Organisms, Clinical Course and Complications of Pyogenic Meningitis in Children - Rai Muhammad Asghar, Zeeshan Ghani , Muddassir Sharif (Journal of Rawalpindi Medical College, 2008)
pyogenic meningitis, monitor clinical course and assess complications. Methods: The study was conducted in Paediatric department of Rawalpindi General Hospital, Rawalpindi, over a period of 1 year. Thirty patients were enrolled in the study. History, complete examination, routine investigations, blood culture and cerebrospinal fluid (CSF) routine examination and culture were performed. Cranial ultrasound and CT scan of brain were performed in selected patients. Treatment was given for ten days, and after discharge patients were followed upto 6 months. Data was entered and analyzed using computer programme SPSS version 10.0. Results: Mean age of patients was 40 + 39.2 months. Eighteen (60%) were male and 12 (40%) were females. The most common clinical presentation was fever (100 %) with mean duration 3.4 + 0.7 days. Cerebrospinal fluid culture was positive in 12 (40%) patients. The most common organism isolated was Streptococcus pneumoniae in 7 (23.3%).On follow up 6 (20%) patients had hearing loss. Thirteen (43.3%) patients fully recovered after therapy, 15 (50.0%) recovered with complications while 2 (6.6%) patients expired. Conclusion: The clinical features like loss of consciousness, signs of meningeal irritation (SOMI) and signs of raised intracranial pressure (ICP) are significantly associated with morbidity and mortality. The positive CSF culture, cranial ultrasound and CT scan findings are also associated with morbidity and mortality.